Phytochemical and anticandidal efficacy of Olea europaea leaf extract from different cultivars and seasonal variation - Pedram Alimosazadeh; Mohd Sajjad Ahmad Khan; Seyed Javad Sanei (Shahrekord University of Medical Sciences, 2023)
Introduction: Olive (Olea europaea L.) is one of the important agricultural and medicinal tree species. This study aimed to assess the antifungal efficacy of olive leaf extract (OLE) obtained from different cultivars and during different seasons against Candida albicans strains. Methods: OLE was prepared using four olive cultivars ('Koroneiki', 'Mission', 'Rowghani', and 'Zard') obtained in two seasons (spring and autumn) from Golestan province, North of Iran. The phenolic and oleuropein contents of vegetative leaves were measured by colorimetric and HPLC techniques, respectively. The antifungal capacities of OLEs were tested by agar well diffusion and the minimal inhibitory concentration (MIC) was evaluated by micro-dilution assay. Results: The findings of our study showed that the total phenolic (27.45-88.16 mg g-1) and oleuropein (3.64-18.13 mg g-1) contents varied in leaf extracts, respectively. The highest amount was found in 'Koroneiki' and 'Zard' (spring leaves) and the lowest in 'Mission' cultivars (autumn leaves). The inhibition zones and MIC ranged from 1.92 to 15.41 mm and from 6.07 to 27.20 mg mL-1 based on C. albicans strains, respectively. Relationship between total phenolic content as an independent variable (X) and inhibition zones or MIC as dependent variables (Y) fitted polynomial curves. Conclusion: The present study highlighted the phytochemical and anti-candidal efficacy of OLE derived from olive cultivars or the seasons of harvested leaves against C. albicans strains. It is suggested that 'Koroneiki' and 'Zard' cultivars, especially during the spring season, could be exploited to isolate potential broad-spectrum antifungal drugs.